2022
DOI: 10.3390/healthcare10122454
|View full text |Cite
|
Sign up to set email alerts
|

Development, Application, and Performance of Artificial Intelligence in Cephalometric Landmark Identification and Diagnosis: A Systematic Review

Abstract: This study aimed to analyze the existing literature on how artificial intelligence is being used to support the identification of cephalometric landmarks. The systematic analysis of literature was carried out by performing an extensive search in PubMed/MEDLINE, Google Scholar, Cochrane, Scopus, and Science Direct databases. Articles published in the last ten years were selected after applying the inclusion and exclusion criteria. A total of 17 full-text articles were systematically appraised. The Cochrane Hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…We hope to conduct additional research in the near future to determine the correlation of ABE formation on orthodontically treated subjects with a history of TM or TP, as well as to investigate the effects of biomechanical force magnitude, force direction, force type (intermittent, continuous), extent of tooth movement, and individual response on changes in alveolar bone thickness over time in different skeletal malocclusions 51,52 …”
Section: Discussionmentioning
confidence: 99%
“…We hope to conduct additional research in the near future to determine the correlation of ABE formation on orthodontically treated subjects with a history of TM or TP, as well as to investigate the effects of biomechanical force magnitude, force direction, force type (intermittent, continuous), extent of tooth movement, and individual response on changes in alveolar bone thickness over time in different skeletal malocclusions 51,52 …”
Section: Discussionmentioning
confidence: 99%
“…The applications of Artificial Intelligence (AI), already showing its footprints in various dental speciality treatments which includes Radiology and diagnosis [15,16], Pediatric Dentistry [17]; Periodontics [18,19]; Implantology [20,21]; Maxillofacial Surgery [22]; Orthodontics [23][24][25]; Prosthodontics [2,[26][27][28][29]; Endodontics [30,31]; and Forensic Odontology [32]. The present study 67.6% participants of the opinion that AI based applications are already using in various dental specialities.…”
Section: (I) Demographic Detailsmentioning
confidence: 80%
“…Several studies on ANN in orthodontics have reported their results on automated cephalometric landmark identification 12,18–25 . Furthermore, commercial orthodontic products for orthodontic diagnosis and treatment evaluation are already in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on ANN in orthodontics have reported their results on automated cephalometric landmark identification. 12,[18][19][20][21][22][23][24][25] Furthermore, commercial orthodontic products for orthodontic diagnosis and treatment evaluation are already in clinical use. Clinicians can choose these AI products and benefit from orthodontic treatment and clinical practice.…”
Section: Discussionmentioning
confidence: 99%